Penggunaan Media Doodle Artistik Dalam Mengembangkan Motorik Halus Dan Seni Pada Anak Kelompok B di TK Tunas Bangsa Sukodono Sidoarjo - Supardi; Hendratno Hendratno; Sri Setyowati (LP. Ma'arif Janggan Magetan, 2023)
This research on the use of artistic doodle media focuses on the development of fine motor skills and art which aims to determine the impact of using artistic doodle media on group B children at Tunas Bangsa Kindergarten, Sukodono District, Sidoarjo Regency. This research is based on the results of preliminary observations which show that teachers are less effective in using instructional media, so that children are less interested in drawing and coloring activities. The research was conducted by using a descriptive qualitative approach which described the data in the form of narrative analysis, and descriptions of the development that would be developed were aspects of fine motor and artistic development in group B children in Tunas Bangsa Kindergarten as many as 15 children. Data collection techniques through observation, interviews, and documentation to strengthen research results. The results of research at Tunas Bangsa Kindergarten, Sukodono District, Sidoarjo Regency found that drawing and coloring activities for group B children used artistic doodle media to attract children's interest in scratching objects from geometric patterns and arranging colorful textures to produce beautiful doodle works. This research is expected to utilize artistic doodle media as an effective learning medium in drawing and coloring activities in the Education Unit and become a reference source for other researchers to use and develop artistic doodle media to make it more interesting